Jaminan Sosial dan Kompensasi: Analisis Perlindungan Pekerja PKWT dalam UU Cipta Kerja - Deviona, Ayu Anggi; Sriono, Sriono; Siahaan, Nimrot (SIGn Jurnal Hukum, 2024)
This study aims to analyze the legal protection afforded to fixed-term employment contract workers under Law Number 6 of 2023, which introduces significant changes to the legal framework governing fixed-term employment in Indonesia. Focusing on working conditions and compensation, this research employs a normative legal research method with a statute approach and utilizes qualitative analysis with a content analysis approach. The findings reveal that Law Number 6 of 2023 establishes a new paradigm in protecting fixed-term employment contract workers by affirming their right to wages during probationary periods, providing flexibility in contract renewals, and regulating the provision of compensation. However, implementing this Omnibus Law also presents new dynamics and challenges, such as the potential for job insecurity due to excessive flexibility in contract extensions. A case simulation further exposes the gap between legal norms and the reality on the ground, where some companies still neglect their obligation to compensate fixed-term employment contract workers. These findings underscore the urgent need for commitment and active participation from all stakeholders, including the government, companies, and workers, in realizing harmonious, productive, and equitable industrial relations.